From IgG Fusion Proteins to Engineered-Specific Human Regulatory T Cells: A Life of Tolerance - Scott, David W. (Frontiers in Immunology, 2017)
Recent efforts have concentrated on approaches to expand and “specify” human regulatory T cells (Tregs) and to apply them to modulate adverse immune responses in autoimmunity and hemophilia. We have used retroviral transduction of specific T-cell receptor, single chain Fv, or antigen domains in Tregs to achieve this goal. Each of these approaches have advantages and disadvantages. Results with these engineered T cells and evolution of the research developments and paths that led to the development of specific regulatory approaches for tolerance are summarized.